Teori Organisasi Klasik - Muh. Sufyan Hadi (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
Education management studies how to manage the education system efficiently and effectively to achieve the goals that have been set. The research method used in this research is a qualitative method, which is based on the philosophy of post-positivism. philosophy of post-positivism. This research aims to explore the relevance and application of classical organizational theory in educational management in the dynamic modern era, by integrating contemporary organizational theories that prioritize human elements, collaboration, and flexibility. The results show that while the basic principles of classical organization theory remain relevant in creating an efficient system in education, it is important to adapt them to the needs of the times. This research contributes to introducing new ways that can improve the effectiveness and efficiency of managing educational organizations by combining the strengths of classical organizational theory and modern theories in facing the challenges of globalization and digitalization.